2014
DOI: 10.1016/j.stemcr.2014.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Human Intestinal Tissue with Adult Stem Cell Properties Derived from Pluripotent Stem Cells

Abstract: SummaryGenetically engineered human pluripotent stem cells (hPSCs) have been proposed as a source for transplantation therapies and are rapidly becoming valuable tools for human disease modeling. However, many applications are limited due to the lack of robust differentiation paradigms that allow for the isolation of defined functional tissues. Here, using an endogenous LGR5-GFP reporter, we derived adult stem cells from hPSCs that gave rise to functional human intestinal tissue comprising all major cell types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 47 publications
0
75
0
Order By: Relevance
“…In contrast, iPSC-derived organoids are more similar to fetal human intestine than adult intestine based on limited gene profiling that compared enteroids generated from human fetal and adult small intestine (19). A recent study reported that adultlike intestinal organoids could be derived from iPSCs; however, these organoids were isolated from iPSCs grown as teratomas to promote differentiation (20). Importantly, the different methods used to generate organoids and maintain their growth in vitro confound comparisons from one study to another.…”
Section: Differentiationmentioning
confidence: 99%
“…In contrast, iPSC-derived organoids are more similar to fetal human intestine than adult intestine based on limited gene profiling that compared enteroids generated from human fetal and adult small intestine (19). A recent study reported that adultlike intestinal organoids could be derived from iPSCs; however, these organoids were isolated from iPSCs grown as teratomas to promote differentiation (20). Importantly, the different methods used to generate organoids and maintain their growth in vitro confound comparisons from one study to another.…”
Section: Differentiationmentioning
confidence: 99%
“…Yet, most of the TG2 ABs' activities where explored in vitro and ex-vivo, very few in animal model but none in vivo, in human. The recently derived adult stem cells, exhibiting functional human intestinal tissue comprising all major cell types of the intestine, can resolve some of the moral aspect of human research [48]. The CD serum contains numerous autoantibodies, IgA-TG2 is only one of them and up till today its differential role in CD induction and maintenance is far from being unraveled.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Watson et al reported, generation of human intestinal organoids (HIOs) in vitro from human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) (McCracken et al 2011 ;Spence et al 2011 ;Forster et al 2014 ). These HIOs develop into mature human intestinal epithelium, where intestinal stem cell maintains crypt villus architecture and human mesenchyme, supported well by mouse vasculature on its grafting.…”
Section: Future Perspectivesmentioning
confidence: 99%